A Nb2CT x MXene-derived M x Preparation method of Nb2O6 / C nanosheets

By slowly oxidizing Nb2CTx MXene into MxNb2O6/C nanosheets, and through heat treatment, the problems of fast capacity attenuation of lithium-sulfur batteries and poor charging and discharge stability of large currents are finally solved, and a high-performance battery separator modified material is realized, improving the cycle stability and capacity retention rate of lithium-sulfur batteries.

CN116854144BActive Publication Date: 2025-04-25NANJING TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310814910.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-04-25
Estimated Expiration
2043-07-03

AI Technical Summary

Technical Problem

The existing lithium-sulfur batteries have fast capacity decays and poor charging and discharge stability during charging and discharging, mainly due to the "shuttle effect" of polysulfides and low catalytic conversion efficiency, and the cumbersome process of traditional composite materials, poor interfacial bonding force of materials, low yield, and complex dimensional and morphological regulation.

Method used

By using Nb2CTx MXene as the precursor, the oxidizing metal salt solution is used to slowly oxidize to form the MxNb2O6/C nanosheet precursor, and finally MxNb2O6/C nanosheets are obtained by heat treatment. The method has simple process, gentle reaction conditions, and uniform micromorphology. The prepared MxNb2O6/C nanosheets have a large specific surface area, rich active sites, good conductivity and uniform morphology.

Benefits of technology

The prepared MxNb2O6/C nanosheets have good catalytic conversion and adsorption during the charging and discharging of lithium sulfur batteries, improving the cycling stability and capacity retention of the battery, and improving the overall performance of the battery due to its special microstructure and conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116854144B_ABST
    Figure CN116854144B_ABST
Patent Text Reader

Abstract

The present invention provides a Nb 2 CT x MXene-derived M x Nb 2 O 6 The method for preparing a single / few-layer Nb / C nanosheet comprises the following steps: first, preparing an oxidizing soluble metal salt solution of a preset concentration as an oxidant solution, then adding the oxidant solution to a single / few-layer Nb / C nanosheet of a preset concentration; 2 CT x In MXene suspension, oxidative metal ions / groups are reacted with single / few-layer Nb 2 CT x MXene was oxidized and then centrifuged, freeze-dried and heat-treated to obtain MXene. x Nb 2 O 6 / C nanosheets. The preparation process of the present invention is simple and easy to operate, the reaction conditions are mild, the microscopic morphology is uniform and controllable, and the prepared M x Nb 2 O 6 / C nanosheets have a large specific surface area, abundant active sites, good conductivity and uniform morphology. They can be used in the fields of battery separator surface modification materials, alkali metal battery materials, supercapacitor materials and nanocatalytic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of two-dimensional material preparation and energy storage, and in particular to a Nb 2 CT x MXene-derived M x Nb 2 O 6 / C nanosheet preparation method. Background Art

[0002] In recent years, with the emergence of new electrical equipment and the improvement of people's living standards, traditional lithium-ion batteries can no longer meet the needs of high-power electrical equipment due to their low energy density and power density. Lithium-sulfur batteries, which have similar charging and discharging mechanisms, high energy density, low electrode material cost, wide sources, and low pollution, are very likely to become the next generation of secondary batteries.

[0003] However, during the charge and discharge process of lithium-sulfur batteries, the "shuttle effect" of polysulfides and their low catalytic conversion efficiency become important limiting factors for the rapid capacity decay and poor high-current charge and discharge stability of lithium-sulfur batteries in actual use. The existing solutions are mainly optimized from the aspects of positive electrode active material and carrier optimization, diaphragm functionalization and new diaphragm development, and electrolyte system regulation. Among them, by modifying the surface of the diaphragm, the diaphragm functionalization is not only simple to operate and low in cost, but also can effectively hinder the shuttling of polysulfides during the battery charge and discharge process, and promote its catalytic conversion, thereby improving the battery charge and discharge efficiency.

[0004] Through investigation, it is found that the current membrane modification for the above problems mostly uses graphene, black phosphorus (BP), two-dimensional transition metal carbon (nitride) (MXene) and other nanomaterials with special microstructures to adsorb and fix polysulfides to inhibit the "shuttle effect" of polysulfides during the charge and discharge process. In addition, some researchers use oxides, sulfides, phosphides, etc. containing Fe, Co, and Ni elements as positive electrode carriers to promote the catalytic conversion efficiency of polysulfides, but most of these compounds have a small specific surface area and poor conductivity. If the above materials are combined and their microstructures are reasonably designed, synergistic enhancement is expected to obtain high-performance Li-S battery positive electrode carriers or membrane modification materials. In recent years, this field has gradually attracted the attention of some researchers, but the current preparation methods of composite materials mostly use physical mixing or hydrothermal / solvothermal in-situ growth methods. The former has a cumbersome preparation process and poor material interface bonding, and the latter has a low yield of prepared materials and a complex size and morphology control process.

[0005] MXene (full name: transition metal carbon (nitride)) is a new type of two-dimensional nanomaterial. It has a large specific surface area, excellent conductivity, and rich and adjustable surface functional groups. It has aroused great interest among researchers in many fields. However, its poor structural stability and easy oxidation limit its application in practice.

[0006] Therefore, those skilled in the art are in urgent need of providing a Nb 2 CT x MXene-derived M x Nb 2 O 6 Preparation method of Nb / C nanosheets 2 CT x MXene is used as a precursor by rationally controlling the concentration, addition amount, dissolution stirring time of the oxidizing metal salt solution, and the effect of Nb 2 CT x The oxidation time, amount of ascorbic acid added, stirring time and other process conditions make Nb 2 CT x Slow oxidation occurs to obtain M x Nb 2 O 6 / C nanosheet precursor, which is then heat treated under specific conditions to obtain M x Nb 2 O 6 / C nanosheets; the preparation process is simple and easy to operate, the reaction conditions are mild, the microscopic morphology is uniform and controllable, and the prepared M x Nb 2 O 6 / C nanosheets have a large specific surface area, abundant active sites, good conductivity and uniform morphology. They can be used in the fields of battery separator surface modification materials, alkali metal battery materials, supercapacitor materials, adsorption materials and nanocatalytic materials. Summary of the invention

[0007] The object of the present invention is to provide a Nb 2 CT x MXene-derived M x Nb 2 O 6 Preparation method of Nb / C nanosheets 2 CT x MXene is used as a precursor by rationally controlling the concentration, addition amount, dissolution stirring time of the oxidizing metal salt solution, and the effect of Nb 2 CT x The oxidation time, amount of ascorbic acid added, stirring time and other process conditions make Nb 2 CT xSlow oxidation occurs to obtain M x Nb 2 O 6 / C nanosheet precursor, which is then heat treated under specific conditions to obtain M x Nb 2 O 6 / C nanosheets; the preparation process is simple and easy to operate, the reaction conditions are mild, the microscopic morphology is uniform and controllable, and the prepared M x Nb 2 O 6 / C nanosheets have a large specific surface area, abundant active sites, good conductivity and uniform morphology. They can be used in the fields of battery separator surface modification materials, alkali metal battery materials, supercapacitor materials, adsorption materials and nanocatalytic materials.

[0008] The present invention provides a Nb 2 CT x MXene-derived M x Nb 2 O 6 The preparation method of / C nanosheets comprises the following steps:

[0009] S1, preparing a preset concentration of oxidizing soluble metal salt solution, adding the oxidizing soluble metal salt solution to the single / few-layer Nb with a preset concentration in a volume ratio of 6:40 within a specific time. 2 CT x The MXene suspension is then stirred at room temperature for a certain period of time to allow the oxidizing metal ions / groups in the oxidizing soluble metal salt solution to react with the single / few-layer Nb 2 CT x Mono- / few-layer Nb in MXene suspensions 2 CT x The nanosheets were oxidized to obtain M x Nb 2 O 6 / C nanosheet precursor suspension;

[0010] S2, the M obtained in step S1 x Nb 2 O 6 A reducing agent solution of preset volume and concentration is immediately added to the precursor suspension of the Nb / C nanosheets to inhibit the oxidative metal ions / groups from reacting with the monolayer / few-layer Nb 2 CT x The nanosheets were further oxidized, stirred for a certain period of time, and the bottom precipitate was collected by centrifugation and freeze-dried to obtain M x Nb 2 O 6 / C nanosheet precursor powder;

[0011] S3, the M obtained in step S2 x Nb 2 O 6 The precursor powder of C nanosheets is heat treated at a specific temperature and time in a preset atmosphere to obtain M x Nb 2 O 6 / C nanosheet powder.

[0012] Preferably, in step S1, the oxidizing soluble metal salt solution is an oxidizing metal ion salt solution or an oxidizing metal group salt solution; the soluble metal salt in the oxidizing metal ion salt solution is any one of ferrous sulfate, ferrous chloride, ferrous nitrate, cobalt sulfate, cobalt chloride, cobalt nitrate, nickel sulfate, nickel chloride, nickel nitrate, ferric sulfate, ferric chloride, and ferric nitrate; the soluble metal salt in the oxidizing metal group salt solution is any one of potassium permanganate, potassium manganate, potassium dichromate, potassium chromate, and potassium vanadate.

[0013] Preferably, in step S1, the solvent of the oxidizing soluble metal salt solution is deionized water, the concentration of the oxidizing soluble metal salt solution is 0.1-1 mol / L, and the volume is 6 ml.

[0014] Preferably, in step S1, a single / few layers of Nb 2 CT x The concentration of MXene suspension was ≤5 mg / ml and the volume was 40 ml.

[0015] Preferably, in step S1, an oxidizing soluble metal salt solution is added to a single / few-layer Nb layer of a preset concentration at a volume ratio of 6:40 within 30 minutes. 2 CT x MXene suspension.

[0016] Preferably, in step S1, the stirring time at room temperature is 10 min to 6 h.

[0017] Preferably, in step S2, the reducing agent solution is an aqueous solution of ascorbic acid.

[0018] Preferably, in step S2, the volume of the reducing agent solution is 5 ml, the concentration is 1-5 mg / ml, and the stirring time is 5-10 min.

[0019] Preferably, in step S3, the preset atmosphere is one of argon or nitrogen.

[0020] Preferably, in step S3, the heating rate during the heat treatment process is 1-5°C / min, the insulation temperature is 400-500°C, and the insulation time is 2-6h.

[0021] The Nb provided by the present invention 2 CT x MXene-derived M x Nb 2 O 6 The preparation method of / C nanosheets has the following advantages:

[0022] 1. The present invention reasonably controls the concentration, addition amount, dissolution stirring time and the amount of Nb 2 CT x The oxidation time, amount of ascorbic acid added, stirring time and other process conditions make Nb 2 CT x Slow oxidation occurs to obtain M x Nb 2 O 6 / C nanosheet precursor, which is then heat treated under specific conditions to obtain M x Nb 2 O 6 / C nanosheets;

[0023] 2. The present invention uses MXene as a precursor to transform it into an oxide / C two-dimensional structure composite material, which can not only maintain the original microstructure and conductive properties of MXene, but also improve its stability; in addition, the oxide obtained after derivatization may also give the composite material special catalytic properties. 2 CT x As a precursor, an oxidizing soluble metal salt solution is used as an oxidant solution in Nb 2 CT x In situ surface induced formation of M x Nb 2 O 6 / C nanosheet precursors and obtain M x Nb 2 O 6 / C nanosheets, not only the preparation process is simple and easy to operate, the reaction conditions are mild, and the microscopic morphology is uniform and controllable, in addition, x Nb 2 O 6 It has dual chemical site adsorption for lithium polysulfide, and bimetallic oxides have more advantages in catalysis and other aspects than traditional monometallic oxides;

[0024] 3. The present invention uses Nb 2 CT x As a niobium source, compared with traditional niobium salts, Nb 2 CT x It has a unique two-dimensional sheet structure, which can provide niobium and also provide a growth template for subsequent derivative products. 2 CTx The excellent electrical properties of the carbon substrate formed by its derivatives are x Nb 2 O 6 Its own electronic transport performance has a good regulatory effect;

[0025] 4. The present invention directly uses oxidizing soluble metal salts and Nb 2 CT x After being dispersed in aqueous solution, it is simply oxidized. This method has sufficient reaction and mild reaction conditions. The slow oxidation of oxidizing metal ions / groups can be used to better control the reaction conditions, thereby obtaining MxNb with controllable micromorphology. 2 O 6 / C nanosheets;

[0026] 5. Compared with the traditional two-dimensional composite material preparation method, this method grows M on the surface of the carbon substrate. x Nb 2 O 6 The M is evenly distributed and uniform in size, and due to its special microstructure, more catalytic active sites are exposed. x Nb 2 O 6 It has a certain catalytic conversion and adsorption effect on polysulfides, and the carbon substrate can effectively improve M due to its excellent conductivity. x Nb 2 O 6 The electron transport of M x Nb 2 O 6 The catalytic performance of the catalyst plays a synergistic role, which significantly improves the performance of lithium-sulfur batteries. In addition, the special microstructure also has a certain gain effect on ion transmission and absorption of electrode material volume expansion.

[0027] 6. The preparation process of the present invention is simple, cost-effective, mild in reaction conditions, and highly safe in the preparation process. The method adopted has strong universality and has important guiding value for the preparation of related materials. x Nb 2 O 6 / C nanosheets retain the microstructure of the precursor, have a large specific surface area, abundant active sites, good conductivity, and uniform morphology. They can be used in the fields of battery separator surface modification materials, alkali metal battery materials, supercapacitor materials, adsorption materials, and nanocatalytic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 For single / few layers of Nb 2 CT xTyndall effect optical photograph of MXene suspension;

[0029] Figure 2 For single / few layers of Nb 2 CT x X-ray diffraction pattern of MXene freeze-dried powder;

[0030] Figure 3 For single / few layers of Nb 2 CT x Scanning electron microscopy image of MXene freeze-dried powder;

[0031] Figure 4 For FeNb in Example 1 2 O 6 X-ray diffraction pattern of / C nanosheets;

[0032] Figure 5-1 For FeNb in Example 1 2 O 6 Low-magnification scanning electron microscopy image of / C nanosheets;

[0033] Figure 5-2 is FeNb in Example 1 2 O 6 High-magnification scanning electron microscopy image of / C nanosheets;

[0034] Figure 6 is FeNb in Example 2 2 O 6 X-ray diffraction pattern of / C nanosheets;

[0035] Figure 7 is FeNb in Example 2 2 O 6 Scanning electron microscopy image of / C nanosheets;

[0036] Figure 8 is FeNb in Example 3 2 O 6 X-ray diffraction pattern of / C nanosheets;

[0037] Figure 9-1 is FeNb in Example 3 2 O 6 Scanning electron microscopy image of / C nanosheets;

[0038] Figure 9-2 is FeNb in Example 3 2 O 6 TEM image of / C nanosheets;

[0039] Fig.10 For FeNb in Example 4 2 O6 X-ray diffraction pattern of / C nanosheets;

[0040] Fig.11 For FeNb in Example 4 2 O 6 Scanning electron microscopy image of / C nanosheets;

[0041] Fig.12 For FeNb in Example 5 2 O 6 Scanning electron microscopy image of / C nanosheets;

[0042] Fig.13 is FeNb in Example 1 2 O 6 / EDS element mapping image of C nanosheets;

[0043] Fig.14 MnNb in Example 6 2 O 6 X-ray diffraction pattern of / C nanosheets;

[0044] Fig.15 MnNb in Example 6 2 O 6 Scanning electron microscopy image of / C nanosheets;

[0045] Fig.16 FeNb in Comparative Example 1 2 O 6 X-ray diffraction pattern of / C nanosheets;

[0046] Fig.17 FeNb in Comparative Example 1 2 O 6 Scanning electron microscopy image of / C nanosheets;

[0047] Fig.18 For FeNb in Comparative Example 2 2 O 6 X-ray diffraction pattern of / C nanosheets;

[0048] Fig.19 For FeNb in Comparative Example 2 2 O 6 Scanning electron microscopy image of / C nanosheets;

[0049] Fig. 20 FeNb in Example 1 and Comparative Examples 3-4 2 O 6 / Optical photograph of C nanosheet precursor powder;

[0050] Fig.21 FeNb in Examples 1 to 4 and Comparative Examples 1 to 22 O 6 / Optical photograph of C nanosheet powder;

[0051] Fig. 22 is the FeNb in Example 1 2 O 6 Comparison chart of cycle stability test of lithium-sulfur battery separator modified with C nanosheets. DETAILED DESCRIPTION

[0052] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.

[0053] The present invention provides a Nb 2 CT x MXene-derived M x Nb 2 O 6 The preparation method of / C nanosheets comprises the following steps:

[0054] S1, prepare a preset concentration of oxidizing soluble metal salt solution, add the oxidizing soluble metal salt solution to the preset concentration of single / few-layer Nb in a volume ratio of 6:40 within 30 minutes. 2 CT x In MXene suspension, single / few-layer Nb 2 CT x The concentration of the MXene suspension is ≤5 mg / ml, and the volume is 40 ml. Then, the suspension is stirred at room temperature for 10 min to 6 h to allow the oxidizing metal ions / groups in the oxidizing soluble metal salt solution to react with the single / few-layer Nb 2 CT x Mono- / few-layer Nb in MXene suspensions 2 CT x The nanosheets were oxidized to obtain M x Nb 2 O 6 / C nanosheet precursor suspension.

[0055] Among them, the oxidizing soluble metal salt solution is an oxidizing metal ion salt solution or an oxidizing metal group salt solution; the soluble metal salt in the oxidizing metal ion salt solution is any one of ferrous sulfate, ferrous chloride, ferrous nitrate, cobalt sulfate, cobalt chloride, cobalt nitrate, nickel sulfate, nickel chloride, nickel nitrate, ferric sulfate, ferric chloride, and ferric nitrate; the soluble metal salt in the oxidizing metal group salt solution is any one of potassium permanganate, potassium manganate, potassium dichromate, potassium chromate, and potassium vanadate.

[0056] The solvent of the oxidizing soluble metal salt solution is deionized water, the concentration of the oxidizing soluble metal salt solution is 0.1-1 mol / L, and the volume is 6 ml.

[0057] S2, the M obtained in step S1 x Nb 2 O 6 A reducing agent solution of preset volume and concentration is immediately added to the precursor suspension of the Nb / C nanosheets to inhibit the oxidative metal ions / groups from reacting with the monolayer / few-layer Nb 2 CT x The nanosheets were further oxidized, stirred for a certain period of time, and the bottom precipitate was collected by centrifugation and freeze-dried to obtain M x Nb 2 O 6 / C nanosheet precursor powder.

[0058] The reducing agent solution is an aqueous solution of ascorbic acid, the volume of the reducing agent solution is 5 ml, the concentration is 1-5 mg / ml, and the stirring time is 5-10 min.

[0059] S3, the M obtained in step S2 x Nb 2 O 6 The precursor powder of C nanosheets is heat treated at a specific temperature and time in a preset atmosphere to obtain M x Nb 2 O 6 / C nanosheet powder.

[0060] Among them, the preset atmosphere is one of argon or nitrogen; the heating rate during the heat treatment process is 1-5°C / min, the insulation temperature is 400-500°C, and the insulation time is 2-6h.

[0061] Example 1

[0062] Embodiment 1 provides a Nb 2 CT x MXene-derived M x Nb 2 O 6 The preparation method of / C nanosheets comprises the following steps:

[0063] Step 1: weigh 1.668 g FeSO 4 7H 2 O was added to a certain volume of deionized water and the volume was adjusted to 6 ml. Stir for 15 min until FeSO 4 7H 2 O was completely dissolved, and then immediately added to 40 ml, 2 mg / ml single / few layer Nb 2 CT xThe suspension was stirred at room temperature for 10 min to allow Fe 2+

[0064] For single / few layers of Nb 2 CT x The nanosheets were oxidized to obtain FeNb 2 O 6 / C nanosheet precursor suspension;

[0065] Step 2: FeNb obtained in step 1 2 O 6 5 ml of 2 mg / ml ascorbic acid solution was added to the precursor suspension of the Fe / C nanosheets to inhibit the 2+ For single / few layers of Nb 2 CT x The nanosheets were further oxidized and stirred for 10 min, then centrifuged at 3500 r / min for 5 min to collect the bottom precipitate, and finally freeze-dried at -40 °C for 24 h to obtain FeNb 2 O 6 / C nanosheet precursor powder;

[0066] Step 3: FeNb obtained in step 2 2 O 6 The precursor powder of / C nanosheets was heat treated in an argon atmosphere, and the temperature was raised to 500℃ at a rate of 3℃ / min and kept at that temperature for 4h to finally obtain FeNb 2 O 6 / C nanosheet powder.

[0067] The single / few-layer Nb used in this example 2 CT x MXene specific characteristics such as Figures 1 to 3 shown. Figure 1 For single / few layers of Nb 2 CT x Tyndall effect optical photograph of MXene suspension. As can be seen from the figure, when laser irradiates Nb 2 CT x It shows obvious Tyndall effect when in suspension, indicating that Nb 2 CT x The suspension is a stable colloidal suspension; Figure 2 For single / few layers of Nb 2 CT x The X-ray diffraction spectrum of MXene freeze-dried powder shows that there are three diffraction peaks at 6.2°(002), 33.1°(100), and 58.6°(110), while Nb 2 The characteristic peak of AlC (38.9°) disappears after etching, which proves that Nb 2 CTx was successfully prepared, and the Nb prepared in this example 2 CT x Higher purity; Figure 3 For single / few layers of Nb 2 CT x Scanning electron microscope image of MXene freeze-dried powder. It can be seen from the figure that the single / few-layer Nb 2 CT x MXene nanosheets are uniform in size and have complete layers.

[0068] Figure 4 The FeNb prepared in Example 1 2 O 6 X-ray diffraction pattern of / C nanosheets. The prepared material is similar to FeNb 2 O 6 The standard card (JCPDS Card No.72-0483) basically matches; Figure 5-1 is FeNb in Example 1 2 O 6 Low-magnification scanning electron microscopy image of / C nanosheets; Figure 5-2 is FeNb in Example 1 2 O 6 / C nanosheets; through analysis, it can be seen that FeNb 2 O 6 / C has a good lamellar structure, and the FeNb 2 O 6 The nanoparticle size is about 50-100 nm, and the distribution is even and the morphology is uniform; Fig.13 is FeNb in Example 1 2 O 6 / C nanosheets. It can be seen from the figure that Nb, C, O and Fe elements are evenly distributed on the surface of the material.

[0069] Example 2

[0070] This embodiment provides a Nb 2 CT x MXene-derived M x Nb 2 O 6 The preparation method of / C nanosheets comprises the following steps:

[0071] Step 1: weigh 1.668 g FeSO 4 7H 2 O was added to a certain volume of deionized water and the volume was adjusted to 6 ml. Stir for 15 min until FeSO 4 7H 2O was completely dissolved, and then immediately added to 40 ml, 2 mg / ml single / few layer Nb 2 CT x The suspension was stirred at room temperature for 2 h to allow Fe 2+ For single / few layers of Nb 2 CT x The nanosheets were oxidized to obtain FeNb 2 O 6 / C nanosheet precursor suspension;

[0072] Step 2: FeNb obtained in step 1 2 O 6 5 ml of 2 mg / ml ascorbic acid solution was added to the precursor suspension of the Fe / C nanosheets to inhibit the 2+ For single / few layers of Nb 2 CT x The nanosheets were further oxidized and stirred for 10 min, then centrifuged at 3500 r / min for 5 min to collect the bottom precipitate, and finally freeze-dried at -40 °C for 24 h to obtain FeNb 2 O 6 / C nanosheet precursor powder;

[0073] Step 3: FeNb obtained in step 2 2 O 6 The precursor powder of / C nanosheets was heat treated in an argon atmosphere, and the temperature was raised to 500℃ at a rate of 3℃ / min and kept at that temperature for 4h to finally obtain FeNb 2 O 6 / C nanosheet powder.

[0074] Figure 6 The FeNb prepared in Example 2 2 O 6 X-ray diffraction pattern of / C nanosheets. The prepared material is similar to FeNb 2 O 6 The standard card (JCPDS Card No.72-0483) is basically consistent. Compared with the X-ray diffraction spectrum of Example 1, the diffraction peak is narrower and the peak intensity is stronger, indicating that FeNb 2 O 6 The grains become larger; Figure 7 The FeNb prepared in Example 2 2 O 6 From the scanning electron microscope image of / C nanosheets, it can be seen that the prepared material partially maintains the two-dimensional nanosheet structure, and obvious holes appear on the sheet layers.

[0075] Example 3

[0076] This embodiment provides a Nb 2CT x MXene-derived M x Nb 2 O 6 The preparation method of / C nanosheets comprises the following steps:

[0077] Step 1, weigh 0.167g FeSO 4 7H 2 O was added to a certain volume of deionized water and the volume was adjusted to 6 ml. Stir for 15 min until FeSO 4 7H 2 O was completely dissolved, and then immediately added to 40 ml, 2 mg / ml single / few layer Nb 2 CT x The suspension was stirred at room temperature for 10 min to allow Fe 2+ For single / few layers of Nb 2 CT x The nanosheets were oxidized to obtain FeNb 2 O 6 / C nanosheet precursor suspension;

[0078] Step 2: FeNb obtained in step 1 2 O 6 5 ml of 2 mg / ml ascorbic acid solution was added to the precursor suspension of the Fe / C nanosheets to inhibit the 2+ For single / few layers of Nb 2 CT x The nanosheets were further oxidized and stirred for 10 min, then centrifuged at 3500 r / min for 5 min to collect the bottom precipitate, and finally freeze-dried at -40 °C for 24 h to obtain FeNb 2 O 6 / C nanosheet precursor powder;

[0079] Step 3: FeNb obtained in step 2 2 O 6 The precursor powder of / C nanosheets was heat treated in an argon atmosphere, and the temperature was raised to 500℃ at a rate of 3℃ / min and kept at that temperature for 4h to finally obtain FeNb 2 O 6 / C nanosheet powder.

[0080] Figure 8 The FeNb prepared in Example 3 2 O 6The X-ray diffraction spectrum of the / C nanosheets shows no obvious diffraction peaks, but a mantou peak appears at about 25°, indicating that the prepared material has poor crystallinity. The complete two-dimensional nanosheets can be seen from the scanning electron microscope image in Figure 9, and obvious lattice fringes can be seen from the TEM image, with a crystal plane spacing of about 0.294nm. 2 O 6 (JCPDS Card No.72-0483), this size is similar to FeNb 2 O 6 (311) crystal plane, indicating that there may be FeNb on the surface of the nanosheet 2 O 6 Particles, because the particles are relatively small, no obvious diffraction peaks appear in the X-ray diffraction pattern.

[0081] Example 4

[0082] This embodiment provides a Nb 2 CT x MXene-derived M x Nb 2 O 6 The preparation method of / C nanosheets comprises the following steps:

[0083] Step 1: weigh 1.668 g FeSO 4 7H 2 O was added to a certain volume of deionized water and the volume was adjusted to 6 ml. Stir for 15 min until FeSO 4 7H 2 O was completely dissolved, and stirring was continued for 30 min. Then, the mixture was immediately added to 40 ml, and 2 mg / ml of monolayer / few-layer Nb 2 CT x The suspension was stirred at room temperature for 10 min to allow Fe 2+ For single / few layers of Nb 2 CT x The nanosheets were oxidized to obtain FeNb 2 O 6 / C nanosheet precursor suspension;

[0084] Step 2: FeNb obtained in step 1 2 O 6 5 ml of 2 mg / ml ascorbic acid solution was added to the precursor suspension of the Fe / C nanosheets to inhibit the 2+ For single / few layers of Nb 2 CT xThe nanosheets were further oxidized and stirred for 10 min, then centrifuged at 3500 r / min for 5 min to collect the bottom precipitate, and finally freeze-dried at -40 °C for 24 h to obtain FeNb 2 O 6 / C nanosheet precursor powder;

[0085] Step 3: FeNb obtained in step 2 2 O 6 The precursor powder of / C nanosheets was heat treated in an argon atmosphere, and the temperature was raised to 500℃ at a rate of 3℃ / min and kept at that temperature for 4h to finally obtain FeNb 2 O 6 / C nanosheet powder.

[0086] Fig.10 The FeNb prepared in Example 4 2 O 6 X-ray diffraction pattern of / C nanosheets. The prepared material is similar to FeNb 2 O 6 The standard card (JCPDS Card No.72-0483) is basically consistent and is relatively close to the X-ray diffraction pattern of Example 1; Fig.11 The FeNb prepared in Example 4 2 O 6 From the scanning electron microscope image of / C nanosheets, it can be seen that most of the prepared materials maintain the two-dimensional nanosheet structure, and the edges of some sheets can no longer maintain the original structure.

[0087] Example 5

[0088] This embodiment provides a Nb 2 CT x MXene-derived M x Nb 2 O 6 The preparation method of / C nanosheets comprises the following steps:

[0089] Step 1: weigh 1.668 g FeSO 4 7H 2 O was added to a certain volume of deionized water and the volume was adjusted to 6 ml. Stir for 20 min until FeSO 4 7H 2 O was completely dissolved, and then immediately added to 40 ml, 5 mg / ml single / few-layer Nb 2 CT x The suspension was stirred at room temperature for 10 min to allow Fe 2+ For single / few layers of Nb 2 CT x The nanosheets were oxidized to obtain FeNb 2O 6 / C nanosheet precursor suspension;

[0090] Step 2: FeNb obtained in step 1 2 O 6 5 ml of 5 mg / ml ascorbic acid solution was added to the precursor suspension of the C nanosheets to inhibit the Fe 2+ For single / few layers of Nb 2 CT x The nanosheets were further oxidized and stirred for 5 min, then centrifuged at 3500 r / min for 5 min to collect the bottom precipitate, and finally freeze-dried at -40 °C for 24 h to obtain FeNb 2 O 6 / C nanosheet precursor powder;

[0091] Step 3: FeNb obtained in step 2 2 O 6 The precursor powder of / C nanosheets was heat treated in a nitrogen atmosphere, and the temperature was raised to 400℃ at 5℃ / min and kept for 4h to finally obtain FeNb 2 O 6 / C nanosheet powder.

[0092] Fig.12 The FeNb prepared in Example 5 2 O 6 Scanning electron microscope image of / C nanosheets shows that the prepared material presents a two-dimensional nanosheet structure, and FeNb 2 O 6 The particles are evenly distributed.

[0093] Example 6

[0094] This embodiment provides a Nb 2 CT x MXene-derived M x Nb 2 O 6 The preparation method of / C nanosheets comprises the following steps:

[0095] Step 1, weigh 0.948g KMnO 4 Add to a certain volume of deionized water and dilute to 6 ml, stir for 15 min until KMnO 4 After complete dissolution, add 2mg / ml mono / little layer Nb to 40ml immediately. 2 CT x The suspension was stirred at room temperature for 10 min to allow MnO 4 - For single / few layers of Nb 2 CT xThe nanosheets were oxidized to obtain MnNb 2 O 6 / C nanosheet precursor suspension;

[0096] Step 2: MnNb obtained in step 1 2 O 6 5 ml of 2 mg / ml ascorbic acid solution was added to the precursor suspension of MnO 4 - For single / few layers of Nb 2 CT x The nanosheets were further oxidized and stirred for 10 min, then centrifuged at 3500 r / min for 5 min to collect the bottom precipitate, and finally freeze-dried at -40 °C for 24 h to obtain MnNb 2 O 6 / C nanosheet precursor powder;

[0097] Step 3: MnNb obtained in step 2 2 O 6 The precursor powder of / C nanosheets was heat treated in an argon atmosphere, and the temperature was increased to 500℃ at a rate of 3℃ / min and kept at that temperature for 4h to obtain MnNb 2 O 6 / C nanosheet powder.

[0098] Fig.14 MnNb in Example 6 2 O 6 X-ray diffraction pattern of / C nanosheets. The prepared material is similar to MnNb 2 O 6 The standard card (JCPDS Card No.72-0484) basically matches; Fig.15 The MnNb prepared in Example 6 2 O 6 Scanning electron microscope image of / C nanosheets. Through analysis, it can be seen that MnNb 2 O 6 / C has a good lamellar structure, and the MnNb 2 O 6 The size of nanoparticles is about 100-150nm.

[0099] Comparative Example 1

[0100] Comparative Example 1 provides a Nb 2 CT x MXene-derived M x Nb 2 O 6 The preparation method of / C nanosheets comprises the following steps:

[0101] Step 1: weigh 1.668 g FeSO 4 7H 2 O was added to a certain volume of deionized water and the volume was adjusted to 6 ml. Stir for 15 min until FeSO 4 7H 2 O was completely dissolved, and then immediately added to 40 ml, 2 mg / ml single / few layer Nb 2 CT x The suspension was stirred at room temperature for 6 h to allow Fe 2+ For single / few layers of Nb 2 CT x The nanosheets were oxidized to obtain FeNb 2 O 6 / C nanosheet precursor suspension;

[0102] Step 2: FeNb obtained in step 1 2 O 6 5 ml of 2 mg / ml ascorbic acid solution was added to the precursor suspension of the Fe / C nanosheets to inhibit the 2+ For single / few layers of Nb 2 CT x The nanosheets were further oxidized and stirred for 10 min, then centrifuged at 3500 r / min for 5 min to collect the bottom precipitate, and finally freeze-dried at -40 °C for 24 h to obtain FeNb 2 O 6 / C nanosheet precursor powder;

[0103] Step 3: FeNb obtained in step 2 2 O 6 The precursor powder of / C nanosheets was heat treated in an argon atmosphere, and the temperature was raised to 500℃ at a rate of 3℃ / min and kept at that temperature for 4h to finally obtain FeNb 2 O 6 / C nanosheet powder.

[0104] Fig.16 FeNb prepared in Comparative Example 1 2 O 6 X-ray diffraction pattern of / C nanosheets. The prepared material is similar to FeNb 2 O 6 The standard card (JCPDS Card No.72-0483) is basically consistent with

[0105] Compared with the X-ray diffraction spectrum of Example 2, the diffraction peak is further narrowed and the peak intensity is stronger, indicating that FeNb 2 O 6 The grains become larger; Fig.17 FeNb prepared in Comparative Example 12 O 6 The scanning electron microscope image of the FeNb / C nanosheet shows that the two-dimensional nanosheet structure of the prepared material has been completely destroyed. 2 O 6 The particles showed obvious agglomeration.

[0106] Comparative Example 2

[0107] Comparative Example 2 provides a Nb 2 CT x MXene-derived M x Nb 2 O 6 The preparation method of / C nanosheets comprises the following steps:

[0108] Step 1: weigh 1.668 g FeSO 4 7H 2 O was added to a certain volume of deionized water and the volume was adjusted to 6 ml. Stir for 15 min until FeSO 4 7H 2 O was completely dissolved, and stirring was continued for 2 h. Then, the mixture was immediately added to 40 ml, and 2 mg / ml of monolayer / few-layer Nb 2 CT x The suspension was stirred at room temperature for 10 min to allow Fe 2+ For single / few layers of Nb 2 CT x The nanosheets were oxidized to obtain FeNb 2 O 6 / C nanosheet precursor suspension;

[0109] Step 2: FeNb obtained in step 1 2 O 6 5 ml of 2 mg / ml ascorbic acid solution was added to the precursor suspension of the Fe / C nanosheets to inhibit the 2+ For single / few layers of Nb 2 CT x The nanosheets were further oxidized and stirred for 10 min, then centrifuged at 3500 r / min for 5 min to collect the bottom precipitate, and finally freeze-dried at -40 °C for 24 h to obtain FeNb 2 O 6 / C nanosheet precursor powder;

[0110] Step 3: FeNb obtained in step 2 2 O 6 The precursor powder of / C nanosheets was heat treated in an argon atmosphere, and the temperature was raised to 500℃ at a rate of 3℃ / min and kept at that temperature for 4h to finally obtain FeNb 2 O 6 / C nanosheet powder.

[0111] Fig.18 FeNb prepared in Comparative Example 2 2 O 6 X-ray diffraction pattern of / C nanosheets. The prepared material is similar to FeNb 2 O 6 The standard card (JCPDS Card No.77-1290) is basically consistent, FeNb 2 O 6 It has transformed into another crystal form; Fig.19 FeNb prepared in Comparative Example 2 2 O 6 Scanning electron microscope image of / C nanosheets shows that the prepared FeNb 2 O 6 Most of them are distributed on the surface of the nanosheets, the distribution is relatively uneven, and the particle sizes are different, indicating that the FeNb prepared under this condition 2 O 6 The material can no longer achieve the experimental purpose.

[0112] Comparative Example 3

[0113] Comparative Example 3 provides a Nb 2 CT x MXene-derived M x Nb 2 O 6 The preparation method of / C nanosheets comprises the following steps:

[0114] Step 1: weigh 1.668 g FeSO 4 7H 2 O was added to a certain volume of deionized water and the volume was adjusted to 6 ml. Stir for 15 min until FeSO 4 7H 2 O was completely dissolved, and then immediately added to 40 ml, 2 mg / ml single / few layer Nb 2 CT x The suspension was stirred at room temperature for 10 min to allow Fe 2+ For single / few layers of Nb 2 CT x The nanosheets were oxidized to obtain FeNb 2 O 6 / C nanosheet precursor suspension;

[0115] Step 2: FeNb obtained in step 1 2 O 6 5 ml of 2 mg / ml ascorbic acid solution was added to the precursor suspension of the Fe / C nanosheets to inhibit the 2+For single / few layers of Nb 2 CT x The nanosheets were further oxidized and stirred for 10 min, then centrifuged at 3500 r / min for 5 min to collect the bottom precipitate, and finally dried in vacuum at 40 °C for 24 h to obtain FeNb 2 O 6 / C nanosheet precursor powder;

[0116] Step 3: FeNb obtained in step 2 2 O 6 The precursor powder of / C nanosheets was heat treated in an argon atmosphere, and the temperature was raised to 500℃ at a rate of 3℃ / min and kept at that temperature for 4h to finally obtain FeNb 2 O 6 / C nanosheet powder.

[0117] Comparative Example 4

[0118] Comparative Example 4 provides a Nb 2 CT x MXene-derived M x Nb 2 O 6 The preparation method of / C nanosheets comprises the following steps:

[0119] Step 1: weigh 1.668 g FeSO 4 7H 2 O was added to a certain volume of deionized water and the volume was adjusted to 6 ml. Stir for 15 min until FeSO 4 7H 2 O was completely dissolved, and then immediately added to 40 ml, 2 mg / ml single / few layer Nb 2 CT x The suspension was stirred at room temperature for 10 min to allow Fe 2+ For single / few layers of Nb 2 CT x The nanosheets were oxidized to obtain FeNb 2 O 6 / C nanosheet precursor suspension;

[0120] Step 2: FeNb obtained in step 1 2 O 6 5 ml of 2 mg / ml ascorbic acid solution was added to the precursor suspension of the Fe / C nanosheets to inhibit the 2+ For single / few layers of Nb 2 CT x The nanosheets were further oxidized and stirred for 10 min, then centrifuged at 3500 r / min for 5 min to collect the bottom precipitate, and finally dried at 40 °C for 24 h to obtain FeNb2 O 6 / C nanosheet precursor powder;

[0121] Step 3: FeNb obtained in step 2 2 O 6 The precursor powder of / C nanosheets was heat treated in an argon atmosphere, and the temperature was raised to 500℃ at a rate of 3℃ / min and kept at that temperature for 4h to finally obtain FeNb 2 O 6 / C nanosheet powder.

[0122] Fig. 20 FeNb in Example 1 and Comparative Examples 3-4 2 O 6 Optical photograph of the precursor powder of / C nanosheets. It can be seen from the figure that compared with freeze drying, the FeNb 2 O 6 The color of the precursor powder of / C nanosheets is obviously abnormal, which may be due to the oxidation of the precursor powder caused by this drying method.

[0123] Fig.21 FeNb in Examples 1 to 4 and Comparative Examples 1 to 2 2 O 6 / C nanosheet powders. It can be seen from the figure that there are differences in powder color. The difference in powder color between Examples 1 to 4 is not obvious, but the difference with Comparative Examples 1 to 2 is more obvious, which also reflects the above results from the side. Fig. 22 is the FeNb in Example 1 2 O 6 Comparison of cycling stability tests of lithium-sulfur battery separators modified with C nanosheets. First, the 0.1A g -1 The unmodified material was activated for one cycle with a current density of 1.004 Å, and the discharge capacity was 1172.05 mAh g -1 The modified discharge capacity is 1268.65 mAh g -1 , the discharge capacity is significantly improved; then at 1Ag -1 The cycle stability test was carried out at a current density of 1.34 W / m, and the first discharge capacity of the unmodified sample was 720.85 mAh g -1 After 90 cycles, the discharge capacity is 559.47 mAh g -1 The capacity retention rate is 77.6%, and the first cycle discharge capacity after modification is 757.78 mAh g -1 After 90 cycles, the discharge capacity is 637.89 mAh g -1 The capacity retention rate is 84.2%, and the cycle stability is also significantly improved.

[0124] In summary, the present invention provides a Nb2 CT x MXene-derived M x Nb 2 O 6 Preparation method of Nb / C nanosheets 2 CT x MXene is used as a precursor by rationally controlling the concentration, addition amount, dissolution stirring time of the oxidizing metal salt solution, and the 2 CT x The oxidation time, amount of ascorbic acid added, stirring time and other process conditions make Nb 2 CT x Slow oxidation occurs to obtain M x Nb 2 O 6 / C nanosheet precursor, which is then heat treated under specific conditions to obtain M x Nb 2 O 6 / C nanosheets; the preparation process is simple and easy to operate, the reaction conditions are mild, the microscopic morphology is uniform and controllable, and the prepared M x Nb 2 O 6 / C nanosheets have a large specific surface area, abundant active sites, good conductivity and uniform morphology. They can be used in the fields of battery separator surface modification materials, alkali metal battery materials, supercapacitor materials, adsorption materials and nanocatalytic materials.

[0125] A person skilled in the art can make various modifications and applications without departing from the essential characteristics of the embodiments. For example, each component detailed in the embodiments can be modified and operated, and the differences related to the modifications and applications can be considered to be included in the scope of protection of the present invention defined by the appended claims.

[0126] The embodiments referred to in this specification mean that the specific features, structures or characteristics described in conjunction with the embodiments are included in at least one embodiment of the present invention. These terms appearing in various places in the specification do not necessarily refer to the same embodiment. In addition, when specific features, structures or characteristics are described in conjunction with any embodiment, it is considered that they fall within the scope of these specific features, structures or characteristics that can be implemented by a person of ordinary skill in the art in conjunction with other embodiments.

Claims

1. A Nb2CT x MXene-derived M x The method for preparing Nb2O6 / C nanosheets is characterized in that: The following steps are involved: S1, prepare an oxidizing soluble metal salt solution with a concentration of 0.1-1 mol / L, and add the oxidizing soluble metal salt solution to the single / few-layer Nb2CT with a preset concentration in a volume ratio of 6:40 within 30 minutes. x The MXene suspension is then stirred at room temperature for 10 min to 2 h to allow the oxidizing metal ions / groups in the oxidizing soluble metal salt solution to react with the single / few-layer Nb2CT x Single / few-layer Nb2CT in MXene suspensions x The nanosheets were oxidized to obtain M x Nb2O6 / C nanosheet precursor suspension; S2, the M obtained in step S1 x A reducing agent solution of preset volume and concentration is immediately added to the Nb2O6 / C nanosheet precursor suspension, wherein the reducing agent solution is an aqueous solution of ascorbic acid, thereby inhibiting the oxidative metal ions / groups from reacting with the single / few-layer Nb2CT x The nanosheets were further oxidized, stirred for a certain period of time, and the bottom precipitate was collected by centrifugation and freeze-dried to obtain M x Nb2O6 / C nanosheet precursor powder; S3, the M obtained in step S2 x The Nb2O6 / C nanosheet precursor powder was heat treated in argon or nitrogen at a specific temperature and time to obtain M x Nb2O6 / C nanosheet powder; wherein, the heating rate during the heat treatment process is 1∼5 ℃ / min, the holding temperature is 400∼500℃, and the holding time is 2∼6 h.

2. Nb2CT according to claim 1 x MXene-derived M x The method for preparing Nb2O6 / C nanosheets is characterized in that: In step S1, the oxidizing soluble metal salt solution is an oxidizing metal ion salt solution or an oxidizing metal group salt solution; the soluble metal salt in the oxidizing metal ion salt solution is any one of ferrous sulfate, ferrous chloride, ferrous nitrate, cobalt sulfate, cobalt chloride, cobalt nitrate, nickel sulfate, nickel chloride, nickel nitrate, ferric sulfate, ferric chloride, and ferric nitrate; the soluble metal salt in the oxidizing metal group salt solution is any one of potassium permanganate, potassium manganate, potassium dichromate, potassium chromate, and potassium vanadate.

3. Nb2CT according to claim 2 x MXene-derived M x The method for preparing Nb2O6 / C nanosheets is characterized in that: In the step S1, the solvent of the oxidizing soluble metal salt solution is deionized water, and the volume of the oxidizing soluble metal salt solution is 6 ml.

4. Nb2CT according to claim 1 x MXene-derived M x The method for preparing Nb2O6 / C nanosheets is characterized in that: In step S1, single / few layers of Nb2CT x The concentration of MXene suspension was ≤ 5 mg / ml and the volume was 40 ml.

5. Nb2CT according to claim 1 x MXene-derived M x The method for preparing Nb2O6 / C nanosheets is characterized in that: In step S2, the volume of the reducing agent solution is 5 ml, the concentration is 1-5 mg / ml, and the stirring time is 5-10 min.

Citation Information

Patent Citations

  • Method for synthesizing manganese niobate MnNb2O6 nanosheet

    CN105776337A

  • Nitrogen-doped carbon-coated tin niobate nano material as well as preparation method and application thereof

    CN113675388A